STATUS GIZI BALITA DI DAERAH TERTINGGAL TAHUN 2004 (KAJIAN DATA SKRT 2004) - Felly P. Senewe; Sandjaja Sandjaja (Persagi, 2006)
Nutritional Status of Under-Five In Less Developed Areas (Analysis of Household Health Survey of 2004).Background: Less Developed Areas (LOA) as defined areas that have in part area with low socio-economic status or low access to public services including health. These conditions are unfavourable for growth of children. Aware about these problems may create programs to lift up the quality of human resources in the areas. Therefore, it is important to have information of the nutritional status of under fives in LOA.Objectives: To have information on the nutritional status of under five children in LOA districts.Methods: This exercise used data of household health survey 2004. The samples were classified into wasting, stunting and underweight. Descriptive analysis was conducted to compare the prevalence of wasting, stunting and underweight between LOA and non LOA.Results: The prevalence of wasting, stunting and underweight are higher in LOA as compared to non LOA. Except in urban LOA the prevalence of underweight is 9.1% as compared urban non LOA 11.3%.Keywords: nutritional status, less developed area.